Security for computer networks : an introduction to data security in teleprocessing and electronic funds transfer. - Davies, Donald W. (John Wiley and Sons, 1989)
Data security. Ciphers and their properties. The data encryption standard. Using a block cipher in practice. Authentication and integrity...